Figural graffiti from the basilica of St. Philoxenos at Oxyrhynchus (El-Bahnasa, Egypt) - Martínez García, José Javier; Mascia, Leah (Imafronte, 2023)
Oxyrhynchus represents a key settlement for understanding the phenomena of continuity and transformation in the long transition to Christianity. The importance of this city and its religious panorama even after the Islamic conquest is testified by the wealth of textual and archaeological evidence unearthed over more than one century of archaeological investigations. New essential testimonies are offered by the excavations carried out since 2013 by the Mission of the University of Barcelona within the area of a Christian religious complex (Sector 24), which has led to the discovery of a rich corpus of figural and textual graffiti. Some of this evidence was found painted or scratched on stone slabs, which were probably used in antiquity to seal the underground galleries of this religious building. After a brief introduction to the history of the site and the aforementioned Christian complex, the present contribution will offer an overview of a group of figural graffiti discovered in this area. Their examination in light of the textual and archaeological sources offered by this settlement and considering the parallels provided by other contemporary cultic spaces will offer some glimpses into the social and cultic background of the devotees visiting the holy site and leaving a trace of their passage on the walls of this sanctuary.